Draft Annual Plan 2005-2006 Volume-I Andaman and Nicobar Administration - Planning Commission (Planning Commission, 2005)
Paddy is the main crop grown during Kharif in about 25% of the land available for agricultural purpose. The rice area is mainly restricted in Andaman District where about 11,500 ha. is cultivated under paddy. This area is also utilized for pulses, oilseeds and vegetables in Rabi after harvest of paddy. Such crops are grown under rainfed condition due to lack of proper irrigation facilities. Growing two successive crops of paddy is not common.
Andaman and Nicobar Administration, Planning Department